Evaluation the Effect of Low Level Laser on Sensori-neural Hearing Loss - Aldergazly, Anwaar A.; Khlaif, Hanan Raheem (Al-Nahrain Journal for Engineering Sciences, 2018)
Low Level Laser Therapy (LLLT) is one of biotechnology its useful as produced treatment for diseases that were previously difficult to treat. Some studies claim that an improvement in hearing threshold and tinnitus symptoms by Low Level Laser therapy and others set no significant effect of laser treatment. The aim of this project was to evaluation effect of low level laser (LLLT) treatment on senserinurail hearing loss. The study including 16 patients divided into two groups each group consists of 8patients (first group consist of 14 ear and second group consist of 16 ears), and each group has ?=650nm+532nm and 2.78mW/cm2. The result of this project found statistically significant differences in each group ( before and after laser application) as well as a significant change in the threshold of pure tone audiometry for patients having hearing degree (40-75)dB in each group.